Andrew W. Lo, Adaptive Markets: Financial Evolution at the Speed of Thought - CARSON, Scott Alan (Journal of Economic and Social Thought, 2019)
Abstract. In 1973, Burton Malkiel published A Random Walk Down Wall Street, unquestionably the best-selling book in financial economics written for the popular press. Prior to its publication, it was common among the general public and financial market practitioners to advocate trading strategies that generated super-normal returns for various asset classes. Malkiel synthesized the prevailing academic research that indicated stock returns followed a random-walk, a statistical process that indicates information and events are random, and it is random information announcements behind stock return variation. Keywords. Financial economics, Adaptive markets, Stock market. JEL. B26, C58, D53, G00, G12.